2013
DOI: 10.3802/jgo.2013.24.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Survival of women with ovarian carcinomas and borderline tumors is not affected by estrogen and progesterone receptor status

Abstract: ObjectiveTo examine the patterns of estrogen receptor (ER) and progesterone receptor (PR) expression in borderline ovarian tumors (BOTs) and ovarian carcinomas. We also assessed the disease-free survival (DFS) and overall survival (OS) in women with ovarian carcinoma, in relation to ER and/or PR expression.MethodsWe examined ER/PR expression in 38 BOTs and 172 ovarian carcinomas removed from patients treated at the State University of Campinas-UNICAMP (Brazil), from 1993 to 2008 and followed for up to 60 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Other studies have shown that hormone therapy regimens containing both progestin (synthetic compounds with similar modes of action as progesterone) and estrogen increase the risks for both ovarian cancer (Beral et al, 2007) and borderline ovarian tumours (Morch et al, 2012) to a greater extent than regimes with estrogen only. The results of a recent study showed significantly greater expression of progesterone receptors in serous than in mucinous borderline ovarian tumours, which might explain why we observed an increased risk primarily for serous tumours (Sallum et al, 2013). Additional large epidemiological studies with appropriate reference groups are clearly needed to confirm or reject our findings on progesterone and risk for serous borderline ovarian tumours.…”
Section: Discussionmentioning
confidence: 50%
“…Other studies have shown that hormone therapy regimens containing both progestin (synthetic compounds with similar modes of action as progesterone) and estrogen increase the risks for both ovarian cancer (Beral et al, 2007) and borderline ovarian tumours (Morch et al, 2012) to a greater extent than regimes with estrogen only. The results of a recent study showed significantly greater expression of progesterone receptors in serous than in mucinous borderline ovarian tumours, which might explain why we observed an increased risk primarily for serous tumours (Sallum et al, 2013). Additional large epidemiological studies with appropriate reference groups are clearly needed to confirm or reject our findings on progesterone and risk for serous borderline ovarian tumours.…”
Section: Discussionmentioning
confidence: 50%
“…However, adverse effects or toxicity still occurs. Although ≥90% of serous BOTs are estrogen receptor-positive [ 52 53 ], there are no detailed studies, only case reports, testing the effect of tamoxifen, leuprolide, or anastrozole on these tumors [ 54 ].…”
Section: Is Postoperative Adjuvant Chemotherapy Necessary?mentioning
confidence: 99%
“…The ovaries are the organs responsible for producing sex hormones and the target organs of sex hormones, estrogen and progesterone, and their receptors. How this affects the occurrence and development of ovarian cancer is one of the hotspots of current research (26). Domestic and international reports on the relationship between ER, PR, and clinicopathological features of ovarian cancer are inconsistent.…”
Section: Discussionmentioning
confidence: 99%